Analisis Hukum Terhadap Implementasi Prinsip Itikad Baik Dalam Perjanjian Hak Tanggungan - Rahma, Luthfiah; Amanah, Safitta; Putri, Thyrafi Amelia (Universitas Sang Bumi Ruwa Jurai, 2025)
The principle of good faith is one of the fundamental principles of contract law in Indonesia. This principle is regulated in Article 1338 paragraph (3) of the Civil Code, which emphasizes that an agreement must be executed in good faith. This provision affirms that each party is bound to execute the agreement in accordance with norms of propriety and justice, not solely based on what is written in the contract. Contract law in Indonesia recognizes a fundamental principle that underlies every contractual relationship, namely the principle of freedom of contract, as stipulated in Article 1338 paragraph (1) of the Civil Code. However, freedom of contract is not absolute; rather, it is limited by the existence of the principle of good faith, as affirmed in Article 1338 paragraph (3) of the Civil Code. This article states that an agreement must be executed in good faith. (Ontology) This research method uses a normative juridical approach. The sources and types of data used are primary and secondary data. Data collection through library research. Data processing was carried out by selecting and examining the obtained data for completeness, as well as systematically classifying or grouping the data. The data analysis used was qualitative legal. Soerjono Soekanto defines normative legal research as